Green Roof Cost-Benefit Analysis: Special Emphasis on Scenic Benefits. Issue 3 (14th August 2016) - Nurmi, Väinö; Votsis, Athanasios; Perrels, Adriaan; Lehvävirta, Susanna
Abstract : This article presents a green roof cost-benefit analysis (CBA). Green roofs are roofs which are partially or completely covered by vegetation. We discuss the benefits and costs of light self-sustaining vegetated roofs. The benefits of the ecosystem services (ES) provided by green roofs can be classified into private and public benefits. We apply the selected valuation methods first in Helsinki, Finland and subsequently explain how results can be transferred to other urban locations. Past research and this study show that private benefits are usually not high enough to justify the expensive investment for a private decision maker. However, when the public benefits are added to the private benefits, social benefits are higher than the costs of green roofs in most cases. Past research quantified most types of the benefits, excluding scenic and biodiversity benefits. Scenic benefits denote the intangible benefits that people derive from the presence of green space, including at least aesthetic and psychological ones. In this article, special emphasis is placed on the valuation of the scenic benefits; these are among the most challenging benefits to valuate in monetary terms. We employ hedonic pricing theory, implemented via spatial regression models, and green roof implementation scenarios in order to estimate the aggregate willingness to pay for a "unit" of green roof. The results show that the scenic benefits can be a significant attribute in cost-benefit calculations. Yet, the amount of benefits strongly depends on the green roof design.